2009
DOI: 10.1007/s10236-009-0222-5
|View full text |Cite
|
Sign up to set email alerts
|

Using the Regional Ocean Modeling System (ROMS) to improve the ocean circulation from a GCM 20th century simulation

Abstract: Global coupled climate models are generally capable of reproducing the observed trends in the globally averaged atmospheric temperature. However, the global models do not perform as well on regional scales. Here, we present results from a 20-year, high-resolution ocean model experiment for the Atlantic and Arctic Oceans. The atmospheric forcing is taken from the final 20 years of a twentieth-century control run with a coupled atmosphere-ocean general circulation model. The ocean model results from the regional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…2b,d), as also found in CMIP3 models in a previous study28. Under the same atmospheric forcing, a high-resolution regional ocean model simulates stronger mean state HT BSO than a low-resolution global model does29.…”
Section: Resultssupporting
confidence: 80%
“…2b,d), as also found in CMIP3 models in a previous study28. Under the same atmospheric forcing, a high-resolution regional ocean model simulates stronger mean state HT BSO than a low-resolution global model does29.…”
Section: Resultssupporting
confidence: 80%
“…Melsom et al . [] showed that heat transports into the Barents Sea were improved by oceanic downscaling and increased resolution. Therefore, higher resolution may improve sea ice area in global climate models, but precautions should be taken with regard to parameterizations of processes that depend on model resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, they also lack important shelf sea physical processes like turbulent mixing, overflows, fronts and a realistic description of the bathymetry and the coastline. Hence, there is an increasing need to use regional/local ocean models to provide valuable, high-resolution information to governments, stakeholders and coastal engineers (Å dlandsvik and Bentsen 2007;Melsom et al 2009;Holt et al 2010;Brown et al 2010).…”
Section: Introductionmentioning
confidence: 99%